The hunt for the Blue tree monitor on Batanta Island, Indonesia: Subsistence on a treasure? - Evy A. Arida; Alamsyah E. N. Herlambang; Mulyadi Mulyadi (Journal of Tropical Ethnobiology, 2021)
The tree monitors, Varanus (Hapturosaurus) are highly valued in international pet trade. These lizards are somewhat striking in their colouration, among which is the Blue tree monitor, Varanus macraei. Body colouration of this species is dominantly blue, which is unique to this monitor lizard species. This distinctive colouration together with its limited distribution has put the species as high-priced export commodity for at least 20 years. Because the lizard is endemic to Batanta Island and the nearby islets in the Raja Ampat Islands, Indonesia, we made a trip to the islands in 2019. We visited the village of Amdui on Batanta, where we made several casual interviews with hunters. Here we report results of our interviews and brief survey on the habitats of V. macraei, in order to identify the roles of local hunters in the trade of tree monitors for international pet markets. Some residents of Amdui have been in search for Blue tree monitors and other monitor lizard species since mid1990s and continue their hunt until very recently for fast cash. Because hunting is yet a large part of their culture more than farming, villagers rely on this method for subsistence. We recommend a socio-cultural approach to inform hunters on the idea of sustainability of harvest, for which a stable livelihood will be a possible consequence.